Calculating Cornell Voltage from Nonstandard Chest Electrode Recording site in the Reasons for Geographic And Racial Differences in Stroke (REGARDS) Study - Soliman, Elsayed Z (2009)
BACKGROUND: To minimize participants’ burden and the need for disrobing, a 7-lead electrocardiogram (ECG) recording using a single mid-sternal chest lead was recorded at the initial stages of The REasons for Geographic And Racial Differences in Stroke (REGARDS) Study. ECG-detected left ventricular hypertrophy (ECG-LVH) by Cornell voltage (RaVL +SV3) cannot be assessed from this method because of the absence of V3. We examined the possibility that the S wave amplitude in the mid-sternal lead (SV) could be used as a surrogate for SV3. METHODS: The REGARDS study is a US national study where 7-lead ECGs were performed in 8,330 (29%) participants and standard 12-lead EGCs were performed in 20,811 (71%). Cornell voltage was calculated as the sum of aVL amplitude + SV (in the 7-lead group) or SV3 (in the 12-lead group). Logistic regression analysis was used to examine and compare the magnitude of the association between the LVH risk factors with ECG-LVH in both groups, and Cox Proportional Hazards analysis was used to examine and compare the hazard ratios of overall mortality and cardiovascular mortality associated with ECG-LVH in both groups. RESULTS: Regardless of the Cornell voltage calculation method, ECG-LVH was significantly associated with LVH risk factors, and with the exception of sex there was no evidence of a difference in the magnitude of the association. ECG-LVH from both approaches were significantly and similarly associated with both all cause and cardiovascular mortality. CONCLUSION: ECG-LVH by Cornell voltage calculated from a 7-lead ECG (using SV in the formula) has demographic and clinical associations that are similar to that calculated from a standard 12-lead ECG (using SV3). In epidemiologic studies recording 7-lead ECG, SV could be used as an alternative to SV3 in the Cornell voltage formula.